Operational Management in the Digital Era: Strategic Integration with Entrepreneurship - Imam Wibowo (Sean Institute, 2023)
The digital era has changed the business paradigm significantly, especially with the adoption of information technology and the emergence of digital entrepreneurship. This research aims to investigate the impact of the digital era and entrepreneurial development on company operational management. This research uses a qualitative approach with descriptive methods. The research results highlight that operational management is not only about production efficiency, but also strategic integration to respond to market dynamics. The findings show that successful entrepreneurial companies are those that are able to integrate new technologies, innovate products and services, and consider social and environmental responsibility. The ability to adapt to market changes quickly, restructure production processes, and improve product or service quality is the main key in building company resilience. The results of this research provide a valuable contribution in designing responsive and adaptive operational management strategies to face future business challenges.